Choice deferral and ambiguity aversion - Igor Kopylov (Theoretical Economics, 2009)
When confronted with uncertain prospects, people often exhibit both choice deferral and Ellsberg-type ambiguity aversion. This paper obtains a joint representation for these behavioral phenomena. The decision maker as portrayed by my model is willing to choose an uncertain prospect f over g rather than to defer this choice if and only if the expected utility of f is greater that or equal to the expected utility of g for every probability measure in a convex and closed set Delta. This set is interpreted as a collection of the decision maker's possible future beliefs. When choices cannot be deferred, the decision maker evaluates every uncertain prospect via an epsilon-mixture of the least favorable element in the set Delta and her current probabilistic belief p in Delta. All components of my model are derived from observable preferences in an essentially unique way.
Keywords: D81; D83; 330; Choice deferral; ambiguity aversion; epsilon contamination; multiple priors model; subjective probability; Ellsberg Paradox